Analisis Tutupan Kanopi Dengan Metode Hemispherichal Photography Di Kawasan Hutan Lindung Bukit Barisan I Sub DAS Lubuk Paraku Kota Padang - Oktarina, Talia; Leilani Eka Putri, Irma (Jurnal Serambi Biologi, 2024)
Forests have various ecological functions, such as carbon storage and the hydrological cycle which is an important part of the ecological function of tropical rainforests. One use of identification data based on the condition of forest canopy cover in the future can be developed to determine conditions (forest health), conservation, disaster management and evaluation in forest management. The aim of this research is to determine Canopy Cover Using the Hemispherical Photography Method in the Bukit Barisan I Protected Forest Area, Lubuk Paraku Watershed, Padang City. This research was carried out from December 2022 - January 2023. The research method was a survey method, where the Indarung forest was used as the location. research and trees in the Bukit Barisan I Protected Forest Area, Lubuk Paraku Watershed, Padang City, were used as research objects. Analysis using the Hemispherical Photography method and Glama software. The results of the research show that the canopy cover of the Bukit Barisan I Protected Forest, Lubuk Paraku Sub-Watershed, has the highest value at Forest Station 3 at 86.67% and the Standard Deviation is 4.28% and the smallest is found at Parak Station 1 has a cover of 78.81% and a standard deviation of 4.38%. The canopy cover of all stations is included in the dense category. Keywords : Canopy cover, Hemispherical photography, Forest